Методы адаптивного кодирования для каналов с изменяющимися параметрами - Горбачёв, Виктор Васильевич; Гавриленко, Светлана Юрьевна; Крылова, Виктория Анатольевна (НТУ "ХПИ", 2008)
В статті розглянуті методи адаптивного кодування для каналів з параметрами, що змінюються, для підвищення надійності і достовірності передачі інформації. Одержані для кожного з пропонованих методів аналітичні вирази, що визначають імовірнісні оцінки ступеня адаптації. Зроблені висновки, а також намічені перспективи подальших досліджень.

In the article the methods of the adaptive encoding are considered for ducting with changing parameters for the increase of reliability and authenticity of information transfer. Analytical expressions determining the probabilistic estimations of degree of adaptation are got for each of the offered methods. The conclusions are made, and also the prospect further researches are planned.
Keywords: информационные системы; передача данных; достоверность; свёрточные коды; пакеты ошибок; сети связи